Pengaruh Model Pembelajaran Indeks Card Match (ICM) Terhadap Hasil Belajar pada Mata Pelajaran Pendidikan Pancasila Siswa Kelas IV di UPT SPF SD Inpres Karuwisi 1 - Firdaus Firdaus; Muhajir Muhajir; Musdalifah Syahrir (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research aims to determine the effect of using the Card Match Index model in learning Pancasila Education on the topic of mutual cooperation for Grade IV Students at UPT SPF SD Inpres Karuwisi 1. This type of research is an experimental research in the form of One Group Pretest-Posttest Design, which is an experiment that in its implementation only involves one class as an experimental class without a control class. The sample studied was 18 students of grade IVA UPT SPF SD Inpres Karuwisi 1 Makassar City. The data collection instruments used in this study were written tests in the form of essays, initial tests (pretests) and final tests (posttests) to measure student learning outcomes before and after the application of the card match index model. The data analysis technique used was a descriptive and inferential analysis test. The results of the descriptive statistical analysis of the effect of the positive card match index model, understanding of the material and concepts of Pancasila Education with this card match index model showed better learning outcomes than before the card match index model was applied. The results of the inferential statistical analysis using the t-test formula, it is known that the value obtained is that t count> t table, namely 8.89> 1.73 with the results of the hypothesis H1 accepted. This proves that the use of the card match index model in Pancasila Education learning has an influence on student learning outcomes. The results of the inferential statistical analysis using the t-test formula, it is known that the value obtained is that t count> t table, namely 8.89> 1.73 with the results of the hypothesis H1 accepted. This proves that the use of the card match index model in Pancasila Education learning has an influence on student learning outcomes.